Penataan Sumber Daya Manusia Aparatur di Pemerintah Kota Salatiga - Aziz, Malik Abdul; Mustam, Mochammad (Journal of Public Policy and Management Review, 2017)
Bureaucracy reform is an effort by the government to change the bureaucracy that consists of institutional, human resources apparatus, management system, accountability, monitoring and public service through various ways to create a good governance. Bureaucracy reform is done if the running bureaucracy is reputed unsuccessful that needs a thorough change. The principle of regional autonomy makes local governments have the authority to manage their own areas including implementing bureaucratic reforms. Focus of this research that researchers choose in bureaucratic reform is structuring human resource apparatus. Data collection techniques used in this research are observation, interview and documentation based. Structuring of apparatus human resources in Salatiga City Government is technically performed by Regional Personnel Board (BKD). Structuring of human resources apparatus studied based on Sedarmayanti and Edy Topo Ashari theory consists of 8 elements, namely task, function and proportional task burden, recruitment according to procedure, adequate remuneration, competency standard of office, assessment of individual competence for apparatus, build performance appraisal system, Build or strengthen staffing databases, develop development and training patterns. The results in this study can be concluded that the arrangement of human resources apparatus in Salatiga City has been implemented. But in the implementation there are still constraints faced by the BKD as the organization of personnel management in the area so it can be said still not succeed. It is recommended for Salatiga City Government to improve socialization and training activities for all apparatus, improve supporting equipment, evaluate regulations, eliminate sectoral egos, build database system apparatus online, recruit contract employees, provide training and training, increase the amount of time and trainees and Provide socialization about the mindset and professional work culture.